Internal Forced Migration in Ukraine: Labor Market Impact and Employment Policy - Sled, Oleksandra; Shvets, Iryna; Myroshnechenko, Ganna; Vasiuta, Viktoriia (International Journal of Engineering and Technology, 2018)
The article considers the peculiarities of internal forced migration in Ukraine and its impact on the regional labor markets. The volumes and directions of forced internal displacement by the regions are analyzed. The indicators of employment and unemployment, labor demand and supply in the regional labor markets are investigated. The grouping of internally displaced persons recipient regions has been carried out in order to develop targeted measures for local labor markets regulation. The patterns of labor markets functioning across the groups of recipient regions are revealed. Positive and negative effects of forced internal migration for local labor markets were examined. The main reasons for the difficulties in the forced migrants employment in Ukraine were considered. Recommendations aimed at the effective regional employment policy development are proposed.Â